Destroying a nation : the civil war in Syria - Dam, Nikolaos van (I.B. Tauris & Co. Ltd, 2017)
"Following the Arab Spring, Syria descended into civil and sectarian conflict. It has since become a fractured warzone which operates as a breeding ground for new terrorist movements including ISIS, as well as the root cause of the greatest refugee crisis in modern history. In this important book, the former Special Envoy of the Netherlands to Syria, Nikolaos van Dam, explains the recent history of Syria, covering the growing disenchantment with the Asad regime, the chaos of civil war and the fractures which led to an immense amount of destruction in the refined social fabric of what used to be the Syrian nation, and the rise and expansion of ISIS. Through an in-depth examination of the role of sectarian, regional and tribal loyalties in Syria, van Dam traces political developments within the Asad regime and the various opposition groups from the Arab Spring to the present day, and provides a deeper insight into the conflict and the possibilities and obstacles for reaching a political solution."--Bloomsbury Publishing